An Analysis of the Service Quali Analisis Mutu Pelayanan Perawat pada Pasien Gangguan Jiwa di RSJ Prof. Dr. M. Ildrem Medan - Ahmad, Zidratul Gemilang; Tanjung, Nadya Ulfa; Gurning, Fitriani Pramita (Jurnal Kesehatan Komunitas, 2024)
In the society’s perception, health services still depend on the patient’s status. High-class patients will be given good service, while low-class patients tend not to get the service they should. This study aimed to find out the quality of service of nurses at Prof. Dr. M. Ildrem Medan Psychiatric Hospital, whether they have carried out their duties by Permenkes Number 26 of 2019 concerning the Implementation of Nursing Practice, and whether they meet the service quality aspects of SERVQUAL theory by Parasuraman. This research used qualitative methods with phenomenological research design. The informants in this study consisted of 5 nurses from different fields, namely 2 nurses of the Deputy Head of the Acute Room, 1 nurse of the Deputy Head of the Chronic Room, 1 nurse of the Head of the UPIP Room, and 1 nurse of the Head of the Mental Poly Room. The data in this study were obtained through two stages, namely observation and interviews conducted for two days in March 2024. The data obtained were analyzed by collecting all data, simplifying the data, showing the results, and drawing conclusions. The results showed that the nurses of Prof. Dr. M. Ildrem Medan Psychiatric Hospital have provided services by aspects of SERVQUAL theory, but there are still obstacles in the physical form aspect, where hospital facilities are not fully by standard operating procedures, for example, the lack of completeness of the patient's activity of daily living, the minimum number of nurses, the roof of the building is starting to wear out, the hospital application is not running, and nurse equipment that needs to be repaired, such as drug trolleys. SERVQUAL theory is the basis for providing health services to the community that can foster positive perceptions of the hospital.